2010
DOI: 10.1111/j.1432-2277.2010.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of clopidogrel and everolimus dramatically reduced the development of transplant arteriosclerosis in murine aortic allografts

Abstract: Summary Our group has shown that platelet inhibition with clopidogrel, an antagonist of the P2Y12 adenosine diphosphate receptor on platelets, reduced the formation of transplant arteriosclerosis. The aim of this study was to investigate whether a combination of cyclosporin or everolimus with clopidogrel has a beneficial effect on the development of transplant arteriosclerosis. Fully MHC mismatched C57Bl/6 (H2b) donor aortas were transplanted into CBA.J (H2k) recipients and mice received either clopidogrel alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…In the present experiments, the cells harvested from KO mice showed a significant reduction of migration stimulated by ADP or 2MeSADP in vitro, and diminished accumulation in the transplanted arteries in vivo. This observation is in part supported by recent reports describing that clopidogrel, a P2Y 12 receptor antagonist, reduces transendothelial migration of dendritic cells and microphages within the vessel wall of murine aortic allografts (17,18). Thus, our findings in the present study provide further evidence that, in addition to platelet P2Y 12 receptor-mediated TA progression (13,14), P2Y 12 receptors on other cell types also substantially contribute to the development of TA.…”
Section: Discussionsupporting
confidence: 90%
“…In the present experiments, the cells harvested from KO mice showed a significant reduction of migration stimulated by ADP or 2MeSADP in vitro, and diminished accumulation in the transplanted arteries in vivo. This observation is in part supported by recent reports describing that clopidogrel, a P2Y 12 receptor antagonist, reduces transendothelial migration of dendritic cells and microphages within the vessel wall of murine aortic allografts (17,18). Thus, our findings in the present study provide further evidence that, in addition to platelet P2Y 12 receptor-mediated TA progression (13,14), P2Y 12 receptors on other cell types also substantially contribute to the development of TA.…”
Section: Discussionsupporting
confidence: 90%
“…19 Murine models of vessel transplantation studies usually use the thoracic aorta. 20 The present study characterizes cold storage injury of mouse aorta on functional and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, the P2Y 12 receptor inhibitor clopidogrel showed anti-inflammatory properties aside its known role as anti-thrombotic agent [7,8]. Furthermore previous studies showed the immunological influence of clopidogrel on the reduction of transplant arteriosclerosis in a fully allogeneic murine aortic allograft model via modulation of adhesion molecule and cytokine expression associated with reduced infiltration of DCs and macrophages within the vascular wall [9][10][11]. ApoE −/− mice develop atherosclerotic lesions faster than wild-type mice when fed a high-cholesterol diet and therefore represent an ideal model to investigate platelet adhesion in the development of atherosclerosis [12].…”
Section: Introductionmentioning
confidence: 98%